Investing in diversification: oil industry of Kazakhstan - Makhanov, Sagat S.; Shalbolova, Urpash Zh.; Kim, Yevgeniy G. (Business: Theory and Practice, 2023)
The article analyzes the growth of opportunities for the production of petrochemical products in the Republic of Kazakhstan. The article analyzes the dynamics of global demand for basic petrochemical products over the past 15 years. The aim of the article is to represent the effectiveness of the project on organizing the production of petrochemical products – polypropylene. The objective of the work is to highlight the characteristics of the possibilities of polypropylene production in Kazakhstan (availability of capacities, raw materials, and transport accessibility to world markets). The ways of using polypropylene in the national economy are substantiated. The analysis of the world demand for polypropylene, the structure of its consumption and production in the context of world economic regions, is considered the main world importers and exporters of polypropylene. The effectiveness of the implementation of the investment project to organize the production of polypropylene in Kazakhstan is presented in the form of a predictive analysis of the supply of marketable products to the markets of individual countries: Turkey, Western, Southern and Eastern Europe, China, the Russian Federation. The article also describes the strengths and weaknesses, potential opportunities and risks of the project for the production, sale and export of Kazakhstani polypropylene.